Penyuluhan Bermedia Sosial Dengan Bijak Pada Anggota Bhayangkari Ranting Sawit Cabang Boyolali - Donna Setiawati; Wisnu Sanjaya; Fera Tri Wulandari; Fariyono; Ari Wahyono (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Community service activities through the implementation of counseling activities on the wise use of social media which were attended by Bhayangkari Sawit Branches, Boyolali Regency, took place in 1 (one) day. This counseling activity is expected to get a good response from all parties, both from the police and the Bhayangkari Sawit Branch of Boyolali Regency. Community service activities in the form of counseling on the wise use of social media can provide benefits, including: providing knowledge about social media to Bhayangkari Members is a very good step to equip members to be wise in using social media and in assisting and supervising the use of social media for their children, by knowing the impact of using social media, members can limit the use of social media for their children and with the knowledge gained through outreach activities, members are expected to be able to explain to their children how to use social media effectively. good and useful as a source of information in supporting the activities of the learning process.